FIQH TOLERANSI DALAM PESPEKTIF AL-QUR’AN DEPARTEMEN AGAMA RI - Wahidah, Nur Robi (MAGHZA, 2016)
The purpose of this writing is observation about thematic tafsir about tolerance. Tolerance as main fundamental in Islam which indicate of Islam Nusantara. The basis of tolerance attitude is separate from the teaching which taking from Quran which as guidance for Islamic people in doing their religious activities. In Quran we regularly find the verse that contain of tolerance such as there is no force in religion , it refers to al baqoroh 256 verses, and many other verses. Parallel with Ministry of religion affairs, there are fours things which will elaborate in this paper. Firstly, Verse of tolerance in quran. Secondly, the characteristic of thematic tafseer , Thirdly, Identification of depag’s interpretation of tolerance verse. Fourthly, Building tolerance fiqh base on interpretation of Depag about tolerance verses. By this concept hopefully possible to building tolerance fiqh and it has law position because taking from verse tolerance which is made by Depag.